Negative evaluation bias for positive self-referential information in borderline personality disorder - Winter, Dorina; Schmahl, Christian; Bohus, Martin (PLOS ONE, 2015)
Previous research has suggested that patients meeting criteria for borderline personality disorder (BPD) display altered self-related information processing. However, experimental studies on dysfunctional self-referential information processing in BPD are rare. In this study, BPD patients (N = 30) and healthy control participants (N = 30) judged positive, neutral, and negative words in terms of emotional valence. Referential processing was manipulated by a preceding self-referential pronoun, an other-referential pronoun, or no referential context. Subsequently, patients and participants completed a free recall and recognition task. BPD patients judged positive and neutral words as more negative than healthy control participants when the words had self-reference or no reference. In BPD patients, these biases were significantly correlated with self-reported attributional style, particularly for negative events, but unrelated to measures of depressive mood. However, BPD patients did not differ from healthy control participants in a subsequent free recall task and a recognition task. Our findings point to a negative evaluation bias for positive, self-referential information in BPD. This bias did not affect the storage of information in memory, but may be related to self-attributions of negative events in everyday life in BPD.